Functional Bioplastic Based on Chitosan/Sago Starch (Metroxylon sago) with the Addition of Black Fruit (Haplolobus sp.) Leaves Ethanolic Extract - Agnes Dyah Novitasari Lestari; Muchammad Fauzan Kuri Pasai; Evelina Somar; Dewi Eviane; Gabriella Shine De Kweldju (ALCHEMY Jurnal Penelitian Kimia, 2025)
Bioplastic as an antioxidant and antibacterial packaging has been synthesized from chitosan and sago starch with Black fruit leaves ethanolic extract. The bioplastic synthesis was done by mixing a solution of chitosan, sago starch, glycerol, and ethanolic extract of Black fruit leaves, pouring it into a petri dish, and then drying it in an oven. The bioplastic produced was then characterized using Fourier transform infrared spectroscopy (FTIR). The results show that increasing the weight ratio of chitosan/sago starch increased tensile strength, decreased elongation, decreased thickness, and increased biodegradation time. The addition of ethanolic extract of black fruit leaves reduces tensile strength at a chitosan/starch weight ratio of 4:1, increases tensile strength at a chitosan/starch weight ratio of 1:1, tends to minimize elongation at both Chitosan/starch ratios, tends to increase thickness at a chitosan/starch weight ratio of 4:1, decreases thickness at a Chitosan/starch weight ratio of 1:1, and increases biodegradation time. The best bioplastic formulation in this study found in  CS11E1 (weight ratio of Chitosan/starch 1:1, extract concentration 1%), with a tensile strength of 4.71 MPa, elongation of 29.33%, thickness of 0.07 mm, and biodegradation time of 6 days.